Epidemiology and Clinical Characteristics of Rotavirus and Norovirus Infections in Hospitalized Children Less Than 5 Yaers of Age With Acute Gastroenteritis in Tehran, Iran - Arash Arashkia; Behrooz Nejati; Mahsa Farsi; Somayeh Jalilvand; Alireza Nateghian; Aliakbar Rahbarimanesh; Fereshteh Moshfegh; Nasir Mohajel; Zabihollah Shoja (Acta Medica Iranica, 2020)
Acute gastroenteritis is one of the most important causes of death in children in developing countries which cause by different enteropathogens, including bacteria, viruses, and parasites. Among these, most of the acute gastroenteritis in children are caused by viral infections mainly by rotavirus and norovirus. This study aimed to study the epidemiological and clinical status of acute gastroenteritis resulting from rotavirus and norovirus in children between June 2015 and June 2016 in Iran. A total of 211 stool specimens were collected from Ali Asghar Children's Hospital and Bahrami Children's Hospital in Tehran, from June 2015 to June 2016. The samples were screened by commercial enzyme immunoassay (EIA) Ridascreen kit and real time RT-PCR to detect rotavirus and norovirus genogroups I and II, respectively. The information on demographic and clinical manifestations was collected, and data analyzed using IBM SPSS statistics version 22. Overall, the detection rate of rotavirus was 25.6 %, and for norovirus infection, it was 17.5%. All norovirus positive specimens belonged to genogroup II. Higher rates of rotavirus infections were observed in children from 7 to 24 months, and higher rates of norovirus infections were detected in children from 1 to 12 months. Clinical symptoms were not different between rotavirus and norovirus case-patients. The present study not only highlights the importance of rotavirus and norovirus infections in Iran but also verifies the relevance of norovirus as the cause of severe gastroenteritis in children.